(3hXGFa TgQ QeVGf GdeHGQc haVGFd UjGe SJI GdCjGe HYOg (B/s - (3GdZQjQ, EHQGgje Hf YHO GdYRjR Hf eMeO,s 1322 (3g`(B-1401 (3gLQjs; (3GdZQjQ, EHQGgje Hf YHO GdYRjR Hf eMeO,s 1322 (3g`(B-1401 (3gLQjs ([(3ecGf GdfTQ ZjQ eMOO(B] :s [(3GdfGTQ ZjQ eMOO(B](3,s, 1977)
(3GdJgfFI HbOhe TgQ QeVGf GdeHGQc(B-(3ddUjGe BOGHG jLeYgG MaX GdLhGQM GdXGgQI(B-(3aVd GdUjGe(B.s
(3jdjg hXGFa GdYTQI GdChGNQ ef QeVGf GdeHGQc dfaS GdeDda(B.s
Keywords: (3TgQ QeVGfs; (3GdYHGOGJ (B((3abg ESdGej(B)s; (3GdUhe (B((3ESdGe(B)s